The Effect of Self-Esteem on Happiness of Students in Medan City - Siregar, Marito; Simarmata, Nenny Ika Putri (Jurnal Ilmu Sosial dan Humaniora, 2026)
Student happiness depends not only on academic success but also on the extent to which they accept, value, and evaluate themselves positively. Students with high self-esteem tend to have an optimistic outlook on life, are able to manage stress, and feel satisfied with their lives. The purpose of this study was to determine the effect of self-esteem on happiness among students in Medan. The subjects were active students in Medan from the academic year of 2021-2024, aged 18-22. The sample size for this study was 270 Medan students, drawn using purposive sampling. Data collection used a Likert scale. Data analysis used descriptive analysis and inferential statistics. Hypothesis testing used simple linear regression. The results found a significant effect of self-esteem on happiness among students in Medan, at 0.556 (55.6%). The higher a student's self-esteem, the higher their level of happiness